Organic Certification and Marketing Workshop Proceeding - Tofinga, Mareko P.; Su'a, Semira (IRETA, 2006)
This workshop discussed the rationale of developing organic agriculture which include the raising of consumers’ awareness and health conscious to pay for natural food, concern for environmental protection, economic benefits and health living...